Problematika Status Anak Angkat Di Randublatung Blora Dalam Perspektif Fatwa MUI - Fathonah Kasuwi; M. Ridlwan Hambali (Asy-Syari’ah : Jurnal Hukum Islam, 2022)
This paper discuss the problem of the status of adopted children in Randublatung sub district, Blora, Central Java from the perspective of the MUI Fatwa. The research method in this writing is a combined study of field research and library research. The data oblained by researchers from the results of interviews, field observations and collecting literature or literature related to the theme of the study and presented in a descriptive qualitative form. The results showed that the MUI Fatwa regarding child adoption has been based on authoritative arguments in Islam. Meanwhile, the care for adopted children at Randublatung Blora has been donw well. However, in the procedure, from the perspective of MUI, the adoptive parents have committed a practices that is contrary to the teachings of Islam, namely registering the name of having occupied the biological father on the birth certificate of the adopted child. As a result, such as the family card and diploma of the child, starting from kindergarten to university level diplomas. Keywords: Adoption of children, Randublatung, the MUI fatwa